(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1862)
This article discusses how the decisions of the Council of Constance, 1414-1418, were received by the Scottish religious authorities. The author describes how the declaration of this Council on the subject of who was the true Pope triggered a heated debate among the Scottish clergy. It is also noted that members of the Scottish church were broadly in favour of the treatment of Huss and Jerome (see pp.408-424), and even emulated this example on a heretical preacher in St Andrews in 1433.